PHYTOPHARMACEUTICAL POTENTIALS OF PROSOPIS LAEVIGATA, SYMPLOCOS COCHINCHINENSIS AND NYMPHAEA ALBA: A REVIEW - Matta, Diksha; Nanda, Harshit; Mahalingam, Gayathri (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â Medicinal plants are used from a very long interval of time for treatment of several diseases. In this review, we present detailed information about the diversified medicinal properties of three different plants, namely, Prosopis laevigata, Symplocos cochinchinensis, and Nymphaea alba. The different medicinal properties found in these three unexplored plants can have industrial applications in the treatment of peculiar diseases such as heart attacks and hypercholestriamia. The typical medicinal properties found in these plant's antioxidant, antibacterial, and antimicrobial activity, which suggests that all these plants can be used in drug design and modeling at commercial level. The unique properties of P. laevigata include anti-biofilm and anti-corrosion activities. The exclusive properties found in S. cochinchinensis include anti-snake venom activity and anticancer activity. The rare properties of N. alba include uterotonic and anxiolytic activities. Combining all these activities, we compare all the properties in these plants and hence conclude with the future therapeutic applications in drug design of these plants.